PEMAHAMAN RELEVANSI DISRUPSI DIGITAL DENGAN PROFESI AKUNTAN KEPADA SISWA/I SMA KRISTOFORUS II JAKARTA - Lukman, Hendro; Felicia Aristie (Jurnal Serina Abdimas, 2025)
The rapid development of information technology in the last decade has had an impact on several jobs and professions. One of the professions that has been affected is the accounting profession. However, this does not mean that this profession will be eliminated by automation, robots and artificial intelligence. In fact, information technology can speed up, be more accurate and improve the work of accountants through repetitive and predictable accounting processes. Not all accountant work can be done by automation, robots and artificial intelligence, the touch of an accountant in evaluating and deciding an action from accounting data and information must consider other dimensions such as humans, the environment, nature and others. So that information technology as an accountant's tool to work better. The method of providing an understanding of accounting and profession to students of SMA Krisforus II Jakarta is given in the form of provision or presentation of class 11 students as material for understanding to choose an interest in class 12 and further studies and professions that will be pursued in the future. The result of this activity is quite effective for class 10 high school students who are still hesitant in determining their interests. For schools, this activity can increase students' knowledge of the work of a profession in the real world. ABSTRAK Pesatnya perkembangan tekonologi informasi pada satu decade terakhir ini membawa dampak pada beberapa pekerjaan dan profesi. Salah satu profesi yang berdampak adalah profesi akuntan. Namun, tidak berarti profesi ini akan tereliminasi dengan adanya otomatisasi, robot dan kecerdasan buatan. Bahkan teknologi informasi dapat mempercepat, lebih akurat dan meningkatkan pekerjaan akuntan melalui proses akuntansi yang berulang dan dapat diprediksi. Tidak semua pekerjaan akuntan dapat dilakukan oleh otomatisasi, robot dan kecerdasaan buatan, sentuhan akuntan dalam mengevaluasi dan memutuskan suatu aksi dari data dan informasi akuntansi harus mempertimbangkan dimensi lain seperti manusia, lingkungan, alam dan lainnya. Sehingga teknologi informasi sebagai alat akuntan untuk bekerja lebih baik. Metode pemberian pemahaman akuntansi dan profesi kepada siswa/i SMA Krisforus II Jakarta diberikan dalam bentuk pembekalan atau pemaparan siswa kelas 11 sebagai bahan pemahaman untuk memilih peminatan di kelas 12 dan studi lanjut dan perfesi yang ditekuni kelak. Hasil kegiatan ini cukup efektif bagi siswa/i SMA Kelas 10 yang masih bimbang dalam menentukan peminatan mereka. Bagi sekolah, kegiatan ini dapat meningkatkan pengetahuan siswa/i akan pekerjaan suatu profesi di dunia nyata.